Innovation and empowerment of CNC 2-axis laser use in Jogja Mastercraft in Yogyakarta, Indonesia - Risky Setiawan; Nurman Setiawan; Alfian Ma'arif; Nurul Huda (Universitas Muhammadiyah Malang, 2025)
Indonesia has the most significant percentage of wood producers worldwide, with 31.24% being furniture and handicraft products. Jogja Mastercraft's creative industry, owned by Mr. Iyos, was established in 2015 and has a turnover of 15 million monthly. This business had been impacted by the COVID-19 pandemic, which reduced labor and decreased the price of eyewear products and wooden watches. Wooden glasses and watches are handicrafts that have high value and are made from the primary material of wood waste. So that if sold and marketed, it has high potential in local and international markets. Some crucial problems are caused by Jogja Mastercraft partners using a manual process in making body bezels and cases on watches and frames on wooden glasses. This makes the product work up to 6 hours, and making glass frames takes 4 hours. In addition, the work on the bezel and case with a scroll saw machine also makes the final result less neat and precise. The second problem is that there are no effective marketing methods and strategies for increasing the sales figures of wooden watch products, so a Joomla-based e-commerce website is needed so that wooden watch sales can be optimal. The main methods and outputs carried out in the implementation of Community Empowerment (PBM) include the application of CNC (Computer Numerically Controlled) technology through the manufacture of laser-type CNC designs with two axes to increase productivity and quality of bezels and cases from wood clocks, provide training and guidance in managing effective marketing management and product promotion, and produce e-commerce websites.